1996
DOI: 10.1139/m96-058
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of resin acid degrading bacteria found in effluent from a bleached kraft pulp mill

Abstract: Thirteen resin acid degrading bacteria enriched on abietic or dehydroabietic acids were isolated from waste water from the aerated stabilization basin of a bleached kraft pulp mill. Standard biochemical tests were used to characterize each isolate. Each isolate was tested for its ability to degrade six abietane- and pimarane-type resin acids. Resin acid concentrations were determined by high pressure liquid chromatography and UV absorbance. Cluster analysis based on phenotypic characteristics identified two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…P450s are heme-thiolate proteins that function as the catalytic component of an electron transport chain generally including a ferredoxin and a ferredoxin reductase in bacterial systems (19). A putative P450, encoded by the tdtD gene, that may function in abietane diterpenoid degradation was recently identified in Pseudomonas diterpeniphila A19-6a, another resin acid-degrading bacterium closely related to BKME-9 (17,18). Morgan and Wyndham (17) reported that a tdtD knockout mutant of A19-6a was retarded in its removal of DhA or AbA from its growth medium when compared to that of the wild type.…”
Section: Resin Is Produced By Most Species Of Coniferous Trees Such Amentioning
confidence: 99%
“…P450s are heme-thiolate proteins that function as the catalytic component of an electron transport chain generally including a ferredoxin and a ferredoxin reductase in bacterial systems (19). A putative P450, encoded by the tdtD gene, that may function in abietane diterpenoid degradation was recently identified in Pseudomonas diterpeniphila A19-6a, another resin acid-degrading bacterium closely related to BKME-9 (17,18). Morgan and Wyndham (17) reported that a tdtD knockout mutant of A19-6a was retarded in its removal of DhA or AbA from its growth medium when compared to that of the wild type.…”
Section: Resin Is Produced By Most Species Of Coniferous Trees Such Amentioning
confidence: 99%
“…Series of injections of target compounds in the concentration range 0.01-25 µg ml 1 were used to determine the linear concentration range. Five-point calibration curves were generated daily at 0.5, 1.0, 2.5, 5.0 and 10 µg ml 1 . The repeatability of the method was evaluated by five consecutive injections of 1 µg ml 1 standard solution, and reproducibility was determined by measuring the same standard solution on six different days.…”
Section: Quantificationmentioning
confidence: 99%
“…Resin acids are tricyclic diterpenoids with a carboxylic moiety that can be classified in two groups: abietanes and pimaranes. 1 Abietanes such as abietic and dehydroabietic acids have an isopropyl substituent on C-13, dehydroabietic acid presenting an aromatic ring. Pimaranes, basically pimaric and isopimaric acids, present a vinyl and a methyl group in this position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comamonas testosteroni is a gram-negative bacterium able to use steroids (as well as many other aromatic compounds) as a sole carbon source; it is an attractive model for the study of the mechanisms involved in the mineralization of these bioactive compounds for their removal from the environment (3,5,6,11,19,26,30,37,38). C. testosteroni metabolizes certain steroids through a complex metabolic pathway involving many steps catalyzed by steroid-inducible enzymes (11,26,38,42).…”
mentioning
confidence: 99%